Damage evolution law on the surface field of argillaceous dolomite based on Brazilian test and 3D digital image correlation - Xiaochuan Wang; Delei Yang (Fracture and Structural Integrity)
This paper aims to disclose the damage evolution law of the surface field of argillaceous dolomite. For this purpose, the 3D digital image correlation was combined with the Brazilian test into a new analysis method for the surface field damage evolution of the rock. First, the stress-strain curve of argillaceous dolomite was obtained in Brazilian test, and the strain contours of the key points were acquired by 3D digital image correlation. Then, the standard deviations of the x and y direction strains at the key points during the test were calculated using statistical methods. In addition, the dual damage factor was introduced to quantify the law of the strain statistics and plotted into a curve. Finally, the strains in x and y directions on the horizontal axis ox in the disc center were obtained through elastic mechanical analysis and compared with those measured by 3D digital image correlation in the elastic phase. In this way, the following conclusions were drawn: the argillaceous dolomite exhibited obvious non-homogeneity in the surface field damage evolution. The different phases of the Brazilian test can be determined accurately according to the turning points of the damage factor curve. The fluctuations of the damage factor curve also reveal the features of surface field damage evolution of argillaceous dolomite in Brazilian test. This research shows that the traditional assumption of homogeneity cannot reflect the heterogeneity of the surface field damage evolution of argillaceous dolomite in Brazilian test and provides a quantitative research method for rock damage evolution in that test.